Post-earthquake assessment of liquefaction in Gölbaşı-Adıyaman following the 6 February 2023 Kahramanmaraş earthquakes: field observations, SPT-based analysis, and laboratory testing of soil ejecta - Zeybek, Abdulhakim; Yildiz, Ozgur; Sonmezer, Yetis Bulent (SPRINGER, 2025)
The 6 February 2023 Kahramanmara & scedil; earthquake sequence (Mw 7.8 and 7.6) triggered extensive liquefaction-induced damage in G & ouml;lba & scedil;& imath; town, Ad & imath;yaman, T & uuml;rkiye. Surface manifestations such as settlements, building tilting and toppling, bearing capacity failures, fissures, and soil ejecta provided clear evidence of cyclic soil liquefaction. This study aims to examine the factors contributing to the observed damage and to better understand liquefaction mechanisms affecting fine-grained soils in the region. A detailed post-earthquake field reconnaissance was conducted to document damage patterns and collect soil ejecta for laboratory analysis, including particle size distribution and cyclic triaxial testing. A comprehensive geotechnical database was compiled from 91 boreholes, complemented by seismic, geological, and topographic data. Liquefaction susceptibility of fine-grained soils was evaluated using laboratory-based criteria, including grain size distribution and Atterberg limits. Standard Penetration Test (SPT-N)-based deterministic and probabilistic models were employed as informative tools to interpret liquefaction triggering potential and associated deformations, including vertical settlements and lateral displacements. A peak ground acceleration of 0.45 g was adopted based on regional seismic assessments. Stress-controlled cyclic triaxial tests conducted on soil ejecta revealed that fine-grained soils with moderate to high plasticity exhibited cyclic liquefaction. The most severe deformation occurred near Lake G & ouml;lba & scedil;& imath;, where loose, saturated, fine-grained alluvial deposits prevail. The findings highlight the complexity of liquefaction in fine-grained soils and emphasize the importance of site-specific investigations and refined assessment methods in seismically active, geologically complex environments.
Keywords: Cyclic soil liquefaction; Liquefaction-induced deformations; Liquefaction assessment; SPT-N-based methods; 2023 Kahramanmara & scedil; earthquakes; G & ouml; lba & scedil; & imath; town; STANDARD PENETRATION TEST; EAST ANATOLIAN FAULT; ACTIVE TECTONICS; SUSCEPTIBILITY; PREDICTION; RESISTANCE; GEOMETRY; STRESS; MODELS; TURKEY; Geology; Meteorology & Atmospheric Sciences; Water Resources